Analisis Psikologi Sastra Tokoh Lian dalam Novel Nyawakarya Vinca Callista - Rita Sutiari, Ni Wayan; Cika, I Wayan; Soreyana, I Made (Humanis, 2016)
This study analyzed the novel Nyawa by Vinca Callista using psychology approach that focuses on the study of psychology of literature and psychological conflict. The issues that were analyzed in the study are (1) How is the structure of novel Nyawa including its characterization, plot, and setting (2) How is the psychological aspect of Lian in novel Nyawa by Vinca Callista (3) How is the psychological conflict of Lian in novel Nyawa by Vinca Callista. The theories used in this study were the structural theory, psychology of literature theory, and conflict theory. Structural theory was used to analyzed the intrinsic elements, while the psychology theory of literature was employed to assess the psychological aspect of Lian in novel Nyawa. To analyzed instrinsic elements, a theory proposed by Nurgiyantoro was used, while on the other hand, a theory proposed by Minderop, Atmaja, Kartono, Endraswara, Teeuw was used to analyzed the psychological aspect of Lian. Also a theory proposed by Minderop and Emzir was used to analyzed the psychological conflict of Lian.